Prevalence and determinants of income among people with disabilities in Nepal: A cross-sectional study - Prasanna Poudel (Advances in Medicine, Psychology, and Public Health)
Background: In Nepal, people with disabilities (PWDs) face significant economic challenges, with disparities in income and higher rates of poverty compared to the general population. This study aims to analyze the prevalence of poverty and determinants of income among PWDs, focusing on the impact of government allowances and other socio-economic factors. Methods: Data were collected from 200 PWDs using a purposive sampling method. Information was gathered through face-to-face interviews and structured questionnaires. The analysis utilized the poverty line to assess poverty levels and multiple regression analysis to explore factors influencing income. Results: The study found that 56.5% of PWDs live below the poverty line when government allowances are not considered, compared to 51% with allowances included. Government support was found to decrease the Gini coefficient by 0.10, indicating a reduction in income inequality. Key factors influencing income included education, work hours, experience, and access to assistive devices, while the severity of disability negatively affected income. Conclusion: The findings highlight the critical role of government interventions in reducing poverty among PWDs. Enhanced support for health, education, and employment, as well as targeted policies to improve accessibility and integration, are essential for improving the economic well-being of PWDs in Nepal. The study underscores the need for policies that address the economic and social inclusion of PWDs to mitigate the high rates of poverty within this group.